Ejercicios aeróbicos en el tratamiento fisioterapéutico de adultos hipertensos - Chávez Vaca, Christian Gabriel (2022)
ABSTRACT: High blood pressure or also called arterial hypertension, influences cardiovascular disease. In America, 1.6 million people die yearly from cardiovascular diseases, of whom about 500,000 are under 70 years of age, which is considered a preventable premature death. This documentary research aimed to analyze information on aerobic exercises in the physiotherapeutic treatment of hypertensive adults by reviewing bibliographic sources to verify their efficacy in these patients. The articles were collected from different sources such as PubMed, Science Direct, Google Scholar, and Scielo; 35 papers were selected, determined by the inclusion and exclusion criteria, search strategies, and evaluation using the PEDro scale. Aerobic training in hypertensive adults has a significant impact not only on lowering blood pressure but also on other factors such as maximum oxygen consumption, reduction of body mass, reduction of cardiovascular risks, more resistance to exercise, as well as reducing stress, anxiety, and improving sleep, thus helping the patient to lead a better quality of life. Therefore, physiotherapeutic treatment with aerobic exercise is favorable in hypertensive adults. Keywords: aerobic exercise, hypertensive adult, physiotherapeutic treatment, aerobic training, hypertension, blood pressure, cardiac rehabilitation.